(untitled) (Ciencias de la Ingeniería y Aplicadas, 2023)
The present work is part of the research project related to the projection of demand, power transformer change and load migration in the Santa Water Food Company "ALIAGUASANTA" CIA. LTDA. of the canton of Salcedo, where there were problems in terms of energy supply and quality of energy; as a first step a total survey of information had to be made to know the total installed load, determining that it exceeded the capacity of the transformer, even if the reserve loads were omitted from the analysis, subsequent to this task, the design of the unifilar plans of the electrical distribution of the whole company was carried out to have a better panorama of the distribution system, additional two network analyzers were installed to determine the energy consumption, powers, voltages, currents and assess the level of transformer overload. It could be determined that the transformer was having working periods of 124% of its capacity. Therefore, a new projection of demand was made and a change of transformer was implemented for one of greater capacity, considering the load projected to have reserves and this could be verified through simulation with the new conditions. After the change of the transformer, the design of the transfer panels, the redesign of the distribution system and the updating of the single-line drawings were made, this in order to prevent system collapses and have real information available from the network before possible failures